Owner-Driven Phased Construction: Linking Livability and Housing Standards in Public Housing in the Bicol Region, Philippines - Elizabeth Regina Buena (Contemporary Public Administration Review, 2026)
This is a research study of two public housing developments in the Philippines – Kenny Village in Albay, and Maogma Village in Camarines Sur. It presents the residents’ experiences living in the units for more than a decade, evaluating the space and its components. Because of the considerations on budget, and administration, public housing is governed by standards for Socialized and Economic Housing - B.P. 220, and Fire Code of the Philippines, R.A. 9514. Slightly differing in focus, both dictate the standards to protect life, health, and property. Different institutional arrangements exist for public housing, but most involve the National Housing Authority (NHA), and or the local government units. Ceiling prices are set considering prevailing market conditions. In this study, the livability of the housing units is assessed based on compliance or non-compliance to standards, and residents’ personal evaluation of the units, public facilities, and the overall environment. This follows theories related to residential satisfaction and good quality housing. Based on the results, non-compliance does not automatically mean dissatisfaction of the units, or a design failure but rather an adaptive governance response. Access to public facilities, availability of services, and the social environment increase perceived livability. Residents modify the original units according to changes in family composition, economic capability, lifestyle, etc. This study highlights the need for public housing policies to anticipate such adaptation as part of a more responsive public housing governance and sustainable built environment.